Measuring the Generosity of Unemployment Benefit Systems: Evidence from Hungary and elsewhere in Central Europe - Elena Bardasi; Ana Lasaosa; John Micklewright; Gyula Nagy (Hungarian Academy of Sciences, Institute of Economics, Labour Research Department, 1999)
The paper considers two aspects of the targeting of unemployment benefit systems (a) the probability that benefit is received in the population of those unemployed on standard international criteria of search and availability, and (b) the probability in the population of benefit recipients that search is conducted. The focus is on Hungary but stylised facts for a range of Central European countries and two EU comparators are derived in the first part of the paper. The second part of the paper finds that most of the large decline in coverage of the Hungarian unemployed by insurance benefit (received by only a quarter of the searching stock in 1997) cannot be explained by changes in the composition of unemployment observable in labour force survey data (including unemployment duration). The probability of active search (search other than through a state employment office) is found to be very similar for those receiving insurance and assistance benefit.
Keywords: 330